Corporate Social Responsibility Practise in Indonesia: The Role of Board Diversity and Corporate Governance - Muhammad Arfani Zaidan; Maulida Nurul Innayah; Naelati Tubastuvi; Arini Hidayah (Indonesian Journal of Business Analytics, 2023)
This study aims to determine the effect of board diversity and corporate governance on corporate social responsibility in consumer non-cyclical companies listed on the Indonesia Stock Exchange. This study uses a purposive sampling method in the consumer non-cyclical companies listed on the Indonesia Stock Exchange, which generated 80 companies or 259 company-year observations during 2019-2021. Testing the research hypothesis in this study using panel data regression model analysis. The analysis techniques carried out in this study are descriptive statistical tests (heteroscedasticity test and autocorrelation test) and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study uses a fixed effect regression model to test the relationship between variables in the regression model. The analysis results prove that gender diversity of directors and audit committees has a positive effect on corporate social responsibility. Meanwhile, the educational background of directors and independent commissioners has no effect on corporate social responsibility. In addition, the nationality diversity of directors has a negative effect on corporate social responsibility.